Production process of kHz crystal frequency electronic component

By improving the wafer cleaning, pre-coating treatment, and aging processes, and by using composite cleaning fluid, argon-oxygen plasma pre-cleaning, and mixed atmosphere aging, the problem of silver layer structure damage in kHz crystal frequency electronic components was solved, and frequency stability and batch consistency were improved.

CN121690104APending Publication Date: 2026-03-17SICHUAN CHUANJING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511829884.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-05
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

In the existing manufacturing process of kHz crystal frequency electronic components, the nanoscale potassium salt-organic complex remaining after wafer cleaning is activated under high temperature, leading to damage to the silver layer structure and potential frequency instability. This cannot be mitigated by conventional parameter fine-tuning, affecting product batch consistency and long-term reliability.

Method used

The cleaning process employs a composite cleaning solution (potassium hydroxide, tetrasodium EDTA, sodium silicate, and methyl isobutyl ketone), combined with argon-oxygen mixed plasma pre-cleaning and composite barrier membrane preparation. During the aging process, a mixed atmosphere (nitrogen, hydrogen, and argon) and a honeycomb porous guide plate are used to form a dense and stable barrier layer, inhibiting silver layer oxidation and potassium ion penetration.

Benefits of technology

It effectively removes residues from the wafer surface, improves frequency stability and batch consistency, meets the needs of high-precision electronic devices, and reduces the possibility of silver layer oxidation and structural damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a kHz crystal frequency electronic component production process, and belongs to the technical field of electronic component manufacturing. Comprising the steps of wafer cleaning, film coating, coarse adjustment, wafer feeding, curing, frequency adjustment, press sealing, pin cutting, backflow, wafer sleeving, aging and the like. A compound cleaning solution containing potassium hydroxide, EDTA (Ethylene Diamine Tetraacetic Acid) tetrasodium, sodium silicate and methyl isobutyl ketone is adopted for wafer cleaning, and residual impurities are removed in a gradient manner through five steps of processes of pre-chelation, main cleaning, solvent replacement, weak acid washing and ultrapure water washing in combination with outlet solution monitoring; (2) pre-cleaning by argon-oxygen mixed plasma before coating, activating by pure argon, and preparing a protective film by adopting a composite barrier liquid containing KR-38S, electronic-grade nano Al2O3 and a BHT hydrogen polymerization inhibitor; in the aging stage, a nitrogen-hydrogen-argon mixed atmosphere is adopted, and a honeycomb porous guide plate made of a quartz material is matched, so that the stability of an aging environment is optimized. The technical problems of wafer cleaning hidden residues, silver layer cross-process structure damage, poor frequency stability and the like in the prior art can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of electronic component manufacturing, and particularly relates to a kHz crystal frequency electronic component production process. BACKGROUND

[0002] As a core timing control component of electronic equipment, the production of the kHz crystal frequency electronic component has formed a standardized process chain, which specifically comprises: clamp cleaning, wafer cleaning, silver layer plating, rough adjustment, wafer mounting, solidification, frequency adjustment, pressure sealing, pin cutting, reflow, wafer sleeving, high-temperature aging, testing, marking and ribbon packaging. Among them, wafer cleaning, plating and aging are the core sub-chains that determine the frequency stability of the product and directly affect the electrode conduction performance and crystal resonance characteristics. However, the sub-chain faces certain technical defects in actual mass production implementation, which are as follows: Firstly, the existing wafer cleaning adopts a potassium hydroxide (TFD7)-pure water alkaline system (conventional cleaning temperature 60℃±5℃), and the main target is to remove surface grease and adsorbed impurities. Although the wafer surface still forms a nanoscale residual layer with a thickness of about 5-10nm after cleaning, pure water spraying and drying treatment, the main component of the residual layer is potassium salt generated by the hydrolysis of potassium hydroxide, and the cleaning liquid (such as a system containing KESH-201) is prone to degradation to produce low-carbon carboxylic acid during use. Such organic impurities will combine with potassium salt to form potassium salt-organic complex, which is tightly attached to the wafer surface. Conventional detection methods (such as visual inspection and resistivity testing) cannot identify such nanoscale residues, which will activate the potassium salt-organic complex on the wafer surface when the wafer directly enters the high-temperature environment of 180-200℃: the potassium ion has strong migration, which will break through the initial deposition interface of the silver layer, penetrate to the grain boundary inside the silver layer, interfere with the ordered packing of silver atoms, and cause the uniformity of the silver layer microstructure to be destroyed; during the subsequent 280℃ high-temperature aging process, the organic complex further decomposes to release CO2 and H2O, and such gases continuously contact the silver layer in a closed aging environment, accelerating the oxidation reaction of silver to generate non-conductive phase of silver oxide.

[0003] The above-mentioned silver layer structure abnormality and oxidation problem will directly destroy the stable conduction of the silver layer to the frequency signal, cause the crystal frequency stability hidden danger, and the hidden danger cannot be alleviated through the parameter fine adjustment (such as aging time adjustment and plating power optimization) in the conventional production, finally leading to poor batch consistency of the product and difficult to meet the use requirements of high-precision electronic equipment in long-term reliability.

[0004] Therefore, it is extremely important to provide a kHz crystal frequency electronic component production process which can effectively eliminate the hidden residues of wafer cleaning and inhibit the silver layer plating and high-temperature aging. SUMMARY

[0005] The present application aims to provide a kHz crystal frequency electronic component production process to effectively eliminate wafer cleaning hidden residues, inhibit silver layer plating and high temperature aging problems.

[0006] The present application aims to provide a kHz crystal frequency electronic component production process to effectively eliminate wafer cleaning hidden residues, inhibit silver layer plating and high temperature aging problems. A kHz crystal frequency electronic component production process, comprising wafer cleaning, plating, coarse adjustment, wafer mounting, curing, frequency adjustment, sealing, pin cutting, reflow, wafer covering and aging processes. In the step S1, the wafer cleaning process comprises the following five steps: pre-chelation, main cleaning, solvent replacement, weak acid washing and ultrapure water washing. In the main cleaning step, a composite cleaning solution is used, which comprises potassium hydroxide, EDTA tetrasodium, sodium silicate and methyl isobutyl ketone. After the ultrapure water washing, the potassium ion concentration is ≤0.1 ppm, the TOC concentration is ≤5 ppb, the methyl isobutyl ketone residue is ≤0.1 ppb, and the isopropyl alcohol residue is ≤0.3 ppb. In the step S2, during the solvent replacement to plating process, the wafer is first pre-cleaned by argon-oxygen mixed plasma, and then activated by pure argon. After the activation, the wafer is immersed in a composite barrier solution for treatment, and then dried to form a composite barrier film. The composite barrier solution comprises KR-38S, electronic grade nano-Al2O3 and electronic grade BHT hydrogen inhibitor. In the step S3, the aging process uses a mixed atmosphere composed of nitrogen, hydrogen and argon, and a honeycomb-shaped porous flow guide plate is arranged in the aging box.

[0007] In some embodiments of the present application, in the step S1, the pre-chelation uses a 0.06-0.10wt% EDTA solution, and the weak acid washing uses 0.05-0.07wt% dilute sulfuric acid with a spraying time of 2-4 min. This scheme can effectively remove residual metal impurities and reduce the risk of substrate corrosion, further ensuring the cleanliness and flatness of the wafer surface.

[0008] In some embodiments of the present application, in the step S1, the composite cleaning solution contains 0.4-0.5wt% potassium hydroxide, 0.10-0.15wt% EDTA tetrasodium, 0.02-0.04wt% sodium silicate and 1.5-2.0wt% methyl isobutyl ketone. In some embodiments of the present application, in the step S2, in the argon-oxygen mixed plasma pre-cleaning step, the power is 90-110W, the pressure is 4-6Pa, and the treatment time is 15-25s. In the pure argon activation step, the power is 90-110W, the pressure is 4-6Pa, and the treatment time is 8-12s. The content of KR-38S in the composite barrier solution is 0.20-0.30wt%, the content of electronic-grade nano-Al2O3 is 0.06-0.10wt%, the content of electronic-grade BHT hydrogen polymerization inhibitor is 0.02-0.04wt%, and the solvent is isopropyl alcohol-ultra-pure water; The treatment temperature of the composite barrier solution is 40-50℃, and the treatment time is 5-8min. The thickness of the composite barrier film is 1.8-2.5nm.

[0009] In actual implementation, if the mixing ratio of argon-oxygen, plasma power or treatment time in S2 is improper, a trace amount of residual solvent in S1 may not be completely reacted, and a nanoscale carbon film may still be formed to hinder the combination of the barrier film; if the component ratio of the composite barrier solution is unbalanced, the treatment temperature is too high or too low, or the baking time is insufficient, KR-38S and nano-Al2O3 may not be combined tightly, the film layer may not be dense enough, and it may be difficult to resist the reduction of the -Ti-O-C- bond by hydrogen in the subsequent aging process. By specifying the specific parameters of plasma treatment, the content of each component of the composite barrier solution, the ratio of solvents, and the treatment and baking conditions, the present application can control the impurity removal effect of pre-cleaning and the forming quality of the barrier film, improve the bonding force and thermal stability of the film layer and the wafer surface, and effectively block the potassium ion permeation and silver layer oxidation path.

[0010] As some implementable manners of the present application, in step S3, the mixed atmosphere is composed of 97.0-98.0vol% nitrogen, 1.3-2.2vol% hydrogen and 0.4-1.0vol% argon.

[0011] As some implementable manners of the present application, in step S3, the surface of the honeycomb-shaped porous flow guide plate is treated by an electronic-grade SiO2 ALD coating, and the specific steps are as follows: taking electronic-grade trichlorosilane and oxygen as precursors, depositing a coating with a thickness of 4-10nm on the surface of the honeycomb-shaped porous flow guide plate at 180-220℃.

[0012] In actual implementation, the honeycomb-shaped porous flow guide plate is in a high-temperature mixed atmosphere for a long time, and the surface is easy to adsorb impurity particles and gas decomposition products generated in the aging process, and the airflow scouring may cause the flow guide plate surface to wear and produce debris. These impurities and debris will contaminate the wafer surface and affect the uniformity of gas flow, aggravating the fluctuation of aging temperature. By setting the SiO2 ALD coating, the present application can improve the wear resistance and anti-adsorption ability of the flow guide plate surface, reduce the attachment of impurities and the generation of debris, ensure that the flow guide plate can guide the gas to form a laminar flow state for a long time, and maintain the uniformity of the temperature and atmosphere in the aging oven.

[0013] As one possible implementation of this application, in step S3, the honeycomb porous guide plate is made of quartz material, and it is fixed to the aging chamber wall with quartz bolts, and the gap between the bolts and the chamber wall is filled with high-temperature resistant sealant.

[0014] As some possible implementations of this application, in step S3, the gas flow rate is controlled at 6-10 L / min and the time is 30-40 min during the gas replacement stage, so that the oxygen content in the cavity is ≤35 ppm and the water vapor content is ≤25% RH. The gas flow rate is 2.5-3.5 L / min, and the gas should be kept flowing in until the temperature drops below 45-55℃.

[0015] Compared with the prior art, the beneficial effects of the present invention are: This invention improves three processes—S1 wafer cleaning, S2 pretreatment before coating and preparation of composite barrier film, and S3 aging—effectively addressing issues such as latent residues during wafer cleaning and cross-process structural damage to the silver layer in existing processes. Specifically: S1 wafer cleaning: A composite cleaning solution containing potassium hydroxide, tetrasodium EDTA, sodium silicate, and methyl isobutyl ketone is used. Potassium hydroxide provides an alkaline cleaning environment, which can loosen the grease and inorganic impurities adhering to the wafer surface, creating conditions for subsequent chelation and extraction steps. Tetrasodium EDTA specifically chelates potassium ions, reducing the residue of nano-sized potassium salts. Sodium silicate can preferentially combine with the hydroxyl groups on the surface of the wafer's quartz substrate to form a protective adsorption layer, mitigating the weak reaction between the carboxyl groups of tetrasodium EDTA and the hydroxyl groups on the quartz substrate surface (this reaction will generate trace amounts of Si-EDTA complex, leading to an increase in wafer surface roughness), thus ensuring the smoothness of the wafer surface. Methyl isobutyl ketone selectively removes organic impurities, including low-carbon carboxylic acids produced by the degradation of the cleaning solution and oil-like contaminants adsorbed on the wafer surface. The orderly connection of five steps—pre-chelation, main cleaning, solvent replacement, weak acid washing, and ultrapure water washing—achieves gradient removal of residues. The combination of in-situ laser Raman spectroscopy and online monitoring can capture the levels of solvent and ion residues in a timely manner, preventing trace residues from entering subsequent processes. This provides a clean and stable wafer surface for S2 pretreatment, reducing the risk of cross-process interference from the source.

[0016] S2 Pretreatment before coating and preparation of composite barrier film: Argon-oxygen mixed plasma can react with trace amounts of methyl isobutyl ketone and isopropanol remaining in S1, preventing incomplete decomposition during activation to form a nanoscale carbon film that hinders barrier film bonding. Pure argon activation can enhance wafer surface activity and strengthen barrier film adhesion. In the composite barrier solution, KR-38S constructs the basic barrier framework, and nano-Al2O3 enhances the thermal stability of the film by forming coordination bonds with titanium oxide groups, reducing the risk of film decomposition during high-temperature aging. BHT hydrogen polymerization inhibitor can inhibit the mild reduction reaction of hydrogen with the -Ti-OC- bonds in the barrier film during aging, reducing the decrease in film density caused by titanium oxide bond breakage. The three work together to form a dense and stable protective layer, reducing the risk of potassium ion penetration and silver layer oxidation, and providing reliable interface protection for the coating process.

[0017] S3 Aging: In a mixed atmosphere of nitrogen, hydrogen, and argon, hydrogen can inhibit the oxidation reaction of the silver layer at high temperatures and reduce the formation of non-conductive silver oxide. Nitrogen and argon ensure the stability of the atmosphere and reduce the impact of harmful gases on the silver layer. The honeycomb porous guide plate can guide the mixed gas to form a stable laminar flow state, improve the uniformity of temperature distribution inside the cavity, avoid the adverse effects of local temperature fluctuations on the silver layer structure, and alleviate the problem of uneven aging caused by single gas flow. This step, through the synergy of atmosphere control and structural optimization, further consolidates the process effects of S1 and S2, reduces the possibility of silver layer oxidation and structural damage during aging, and works in conjunction with the composite barrier film to reduce frequency stability risks.

[0018] In summary, this invention not only solves the technical problems mentioned in the background art, but also alleviates derivative problems such as substrate reaction, carbon film contamination, and barrier film deterioration that may occur during process implementation through the linkage of technical features in each step. It helps to improve the frequency stability and batch consistency of kHz crystal frequency electronic components and adapt to the usage requirements of high-precision electronic equipment. Detailed Implementation

[0019] Example 1 S1. Fixture cleaning: Place the quartz fixture in a 5wt% sodium hydroxide solution and ultrasonically clean it at 50℃ for 15 minutes. After cleaning, rinse it with ultrapure water and dry it at 105℃ for 30 minutes.

[0020] S2 chip cleaning: S201. Pre-chelation: Prepare 500 mL of 0.08 wt% EDTA solution, immerse the quartz crystal (specification: 10 mm × 10 mm × 0.5 mm, purity ≥ 99.99%) in the solution, ultrasonically clean it for 10 min at 300 W (temperature 40℃), and then rinse it twice with ultrapure water.

[0021] S202. Main cleaning: Prepare 500mL of composite cleaning solution, which contains 0.45wt% potassium hydroxide, 0.12wt% tetrasodium EDTA, 0.03wt% sodium silicate, 1.8wt% methyl isobutyl ketone, and the balance is ultrapure water; immerse the wafer in the composite cleaning solution and ultrasonically clean it at 300W for 15min (temperature 60℃).

[0022] S203. Solvent replacement: Immerse the wafer in isopropanol for 10 minutes, stirring at a rate of 50 r / min, to remove residual composite cleaning solution from the surface.

[0023] S204. Weak acid wash: Prepare a 0.06wt% dilute sulfuric acid solution, adjust the pH to 3.5, spray the wafer with 0.2MPa pressure for 3 minutes, and rinse twice with ultrapure water.

[0024] S205. Ultrapure water washing: Immerse the wafer in ultrapure water and ultrasonically clean it at 200W for 20 minutes. After removal, monitor it using an in-situ laser Raman spectrometer (detection wavelength 532nm, resolution 2cm). -1 Methyl isobutyl ketone residue ≤0.1ppb, isopropanol residue ≤0.3ppb; online monitoring of the outlet liquid, potassium ion concentration ≤0.1ppm, TOC concentration ≤5ppb, and wafer surface roughness Ra is 0.15nm.

[0025] S3. Pretreatment before coating and preparation of composite barrier film: S301. Argon-Oxygen Mixed Plasma Pre-cleaning: Place the wafer into the plasma processing equipment, introduce argon (flow rate 20 sccm) and oxygen (flow rate 1 sccm), power 100W, pressure 5Pa, processing time 20s.

[0026] S302. Pure argon activation: Maintain pressure of 5 Pa, turn off oxygen, argon flow rate of 20 sccm, power of 100 W, and processing time of 10 s.

[0027] S303. Preparation of barrier film: Immerse the activated wafer in the composite barrier solution (temperature 45℃) for 6 min, remove it and place it in an oven, bake at 130℃ for 25 min to form a composite barrier film with a thickness of 2.2 nm.

[0028] The composite barrier liquid is prepared as follows: Preparation of KR-38S: 100g of polymethylhydrosiloxane (number average molecular weight 1000), 5g of tetrabutyl titanate, and 3g of γ-aminopropyltriethoxysilane were added sequentially to a 500mL three-necked flask. Nitrogen gas was introduced to replace the air in the flask three times. The temperature was raised to 120℃ under a nitrogen atmosphere and the mixture was stirred for 3h. After the reaction was completed, the mixture was cooled to room temperature and then distilled under reduced pressure at 0.08MPa and 80℃ for 30min to remove low-boiling substances, yielding a pale yellow transparent liquid, KR-38S.

[0029] Preparation of electronic-grade nano-Al2O3: 20g of aluminum isopropoxide was slowly added to 100g of anhydrous ethanol and stirred until completely dissolved; 5g of ultrapure water was slowly added dropwise at 40℃, and the pH of the system was adjusted to 3.0 with 0.1mol / L hydrochloric acid, and stirring was continued for 2h to form a homogeneous sol; the sol was placed in a sealed container and aged at 25℃ for 24h, then dried at 105℃ for 12h, and finally placed in a muffle furnace and calcined at 600℃ at a heating rate of 5℃ / min for 3h. After cooling, it was ground to obtain white powdery electronic-grade nano-Al2O3 (particle size detected as 6-10nm).

[0030] Preparation of composite barrier liquid: Weigh 0.25wt% KR-38S, 0.08wt% electronic grade nano Al2O3, and 0.03wt% electronic grade BHT hydrogen polymerization inhibitor, add isopropanol-ultrapure water mixed solvent (volume ratio 8:2), and ultrasonically disperse at 180W for 20min to obtain composite barrier liquid.

[0031] S4. Coating: Place the wafer with the composite barrier film into a vacuum evaporation machine with a vacuum degree of 5×10⁻⁶. -4 Pa was used to vapor-deposit a silver target at a rate of 0.5 nm / s to form a silver electrode with a thickness of 100 nm.

[0032] S5. Coarse adjustment: The silver layer is initially polished using a laser frequency modulator to coarsely adjust the crystal frequency to within ±5ppm of the target frequency.

[0033] S6. Mounting: Fix the coarsely adjusted wafer onto the ceramic substrate using a high-temperature resistant adhesive (temperature resistance ≥300℃) and cure at 120℃ for 30 minutes.

[0034] S7. Curing: Place the base in a curing oven and keep it at 150°C for 2 hours under a nitrogen atmosphere to allow the adhesive to fully cure.

[0035] S8. Frequency modulation: Use the laser frequency modulator again to finely adjust the crystal frequency and control it within the range of ±1ppm of the target frequency.

[0036] S9. Sealing: Place the wafer into a nitrogen-protected sealing machine at a temperature of 200℃, a pressure of 0.3MPa, and a sealing time of 10min to form a sealed cavity.

[0037] S10. Lead trimming: The electrode leads are trimmed using a precision lead trimming machine, retaining a length of 5mm and a lead spacing of 2mm.

[0038] S11. Reflow: Place the product in a reflow oven, heat to 260°C, hold for 10 seconds, and then allow it to cool naturally to room temperature to enhance the adhesion between the leads and the silver layer.

[0039] S12. Sleeve: Sleeve the product into the quartz protective sleeve, with a gap of 0.1mm between the protective sleeve and the product.

[0040] S13. Aging: Gas replacement stage: Place the laminated product into an aging chamber, and place a quartz honeycomb porous baffle plate (60% porosity, 2.0mm upper diameter, 1.8mm lower diameter, fixed with quartz bolts, the gap between the bolts and the chamber wall is filled with high-temperature resistant sealant). Introduce a mixed atmosphere (97.5 vol% nitrogen, 1.8 vol% hydrogen, and 0.7 vol% argon by volume) at a flow rate of 8 L / min for 35 min. Detect the oxygen content in the chamber as 30 ppm and the water vapor content as 20% RH.

[0041] Aging stage: Adjust the gas flow rate to 3.0 L / min, increase the temperature to 280℃ at a rate of 5℃ / min, and hold for 2 hours; Cooling phase: Keep the gas supply running and allow it to cool naturally to below 50°C before shutting off the gas supply.

[0042] S14. Test: Use an impedance analyzer to test the contact resistance of the silver layer, and a frequency meter to test the frequency stability. Record the data.

[0043] S15. Marking: Use a laser marking machine to mark the product model and batch information on the surface of the protective case.

[0044] S16. Tape and reel packaging: Place the product in anti-static tape, arranged at 5mm intervals, seal the package and store in a dry box (humidity ≤30% RH).

[0045] Example 2 Based on Example 1, some parameters were adjusted as follows: S202 Main Cleaning Composite Cleaning Solution: Potassium hydroxide 0.42wt%, Tetrasodium EDTA 0.14wt%, Sodium silicate 0.025wt%, Methyl isobutyl ketone 1.6wt%; S301 plasma pre-cleaning: power 105W, processing time 22s; pure argon activation: power 95W, processing time 11s; S303 composite barrier liquid: KR-38S 0.22wt%, electronic grade nano Al2O3 0.09wt%, processing temperature 48℃, baking time 22min, film thickness 2.0nm; S13 mixed atmosphere: 97.2 vol% nitrogen, 2.0 vol% hydrogen, 0.8 vol% argon; gas replacement flow rate 7 L / min, time 38 min; aging stage flow rate 3.2 L / min.

[0046] The remaining components, parameters, and steps are the same as in Example 1.

[0047] Example 3 Based on Example 1, a SiO2ALD coating was applied to the honeycomb porous guide plate: the quartz honeycomb porous guide plate was placed in an atomic layer deposition apparatus, using electronic-grade trichlorosilane and oxygen as precursors, the deposition temperature was controlled at 200°C, and 50 deposition cycles were performed to form a SiO2ALD coating with a thickness of 8 nm; after the coating was prepared, it was fixed to the aging chamber with quartz bolts as in Example 1, and the gap between the bolts and the chamber wall was filled with high-temperature resistant sealant.

[0048] The remaining components, parameters, and steps are the same as in Example 1.

[0049] Comparative Example 1 Compared to Example 1, the "composite cleaning solution" was replaced with "0.45wt% potassium hydroxide aqueous solution".

[0050] The remaining components, parameters, and steps are the same as in Example 1.

[0051] Comparative Example 2 Compared to Example 1, the composite barrier liquid in step S3 does not contain electronic-grade nano-Al2O3, and the content of the remaining components (electronic-grade BHT hydrogen inhibitor and KR-38S) is the same as in Example 1.

[0052] The remaining components, parameters, and steps are the same as in Example 1.

[0053] Comparative Example 3 Compared to Example 1, the composite barrier liquid in step S3 does not contain electronic-grade BHT hydrogen inhibitor, and the content of the remaining components (KR-38S, electronic-grade nano Al2O3) is the same as in Example 1; The remaining components, parameters, and steps are the same as in Example 1.

[0054] Comparative Example 4 Compared to Example 1, the S13 aging atmosphere was replaced with 100 vol% nitrogen, the gas replacement flow rate was 8 L / min, the time was 35 min, and the flow rate during the aging stage was 3.0 L / min.

[0055] The remaining components, parameters, and steps are the same as in Example 1.

[0056] Experimental Example The kHz crystal products prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to three performance tests. 30 samples were selected from each group as test samples. All 30 samples in each group were tested for all three performances. Before the test, the surface of the samples was wiped with anhydrous ethanol and allowed to air dry. The test results are shown in Table 1 (the three performance data in Table 1 are the average values ​​of the 30 samples).

[0057] The performance tests were conducted in the following order: contact resistance test → frequency stability test → silver layer oxidation rate test after high-temperature aging. The specific test methods for each performance test are as follows: Silver layer contact resistance: An impedance analyzer was used with a test frequency of 1kHz and a test voltage of 0.1V. The test points were selected as the center of the silver layer electrode and the two side edges (3 points evenly distributed with a spacing of 2mm). Each point was tested twice, and the average value of the 6 test results was taken as the contact resistance value of the sample.

[0058] Frequency stability: The target frequency was set to 12MHz. A frequency meter was used to continuously monitor the frequency for 24 hours with a 1-hour test interval, and 24 sets of frequency data were recorded. The deviation of each data from the target frequency was calculated, and the maximum absolute value of the deviation was taken as the frequency stability index of the sample (e.g., if the maximum deviation is 1.2ppm, it is recorded as ±1.2ppm).

[0059] Oxidation rate of silver layer after high-temperature aging: X-ray photoelectron spectroscopy was used for measurement. The test area was the center of the silver layer (diameter 200 μm). The excitation source was Al Kα rays (hν = 1486.6 eV) with a power of 150 W. The binding energy was calibrated based on C 1s (284.8 eV). The Ag 3d and O 1s spectra were fitted using XPS Peak Fit software to calculate Ag 3d and O 1s spectroscopy. + The oxidation rate is equal to the atomic ratio of total Ag = (Ag) + (Number of Ag atoms / Total number of Ag atoms) × 100% (Ag in Ag₂O) + The atomic ratio of silver oxide to O is 2:1, which can be verified by the characteristic peak area of ​​silver oxide in the O 1s spectrum.

[0060] Batch pass rate: 30 samples per group are used as the statistical base. The pass rate is set according to the requirements of the high-precision electronic equipment industry (contact resistance ≤15Ω, frequency stability ≤±3ppm, oxidation rate ≤2%). Only when the sample meets the above three indicators at the same time is it judged as a qualified product. Pass rate = (number of qualified samples / 30) × 100%.

[0061] Table 1: As can be seen from Table 1: Examples 1-2 effectively improve upon existing processes for issues such as latent residues during wafer cleaning, cross-process structural damage to the silver layer, and frequency stability. Specifically, the silver layer contact resistance in both examples is ≤11.5Ω, and the frequency stability is ≤±1.3ppm, mitigating the adverse effects of residual impurities and silver layer oxidation on crystal resonance characteristics. After high-temperature aging, the silver layer oxidation rate is ≤0.9%, reducing the risk of decreased conductivity due to abnormal silver layer structure and oxidation. The batch pass rate is ≥95.3%, improving the problem of poor batch consistency in traditional processes and adapting to the performance requirements of high-precision electronic devices for crystal components.

[0062] Example 3, based on Example 1, introduces a SiO2ALD coating to treat the honeycomb porous flow guide plate, which further improves the flow guide plate's resistance to impurity adsorption and surface stability, reduces the impact of impurity contamination and airflow turbulence on the silver layer during aging, and optimizes the crystal frequency stability and silver layer oxidation resistance related indicators, making it more suitable for the stability requirements of the aging environment in large-scale production.

[0063] In Comparative Example 1, because the traditional potassium hydroxide aqueous solution was used instead of the composite cleaning solution, the chelating effect of sodium EDTA tetrasodium, the protective effect of sodium silicate, and the organic impurity extraction effect of methyl isobutyl ketone were lacking. As a result, the residual potassium salt-organic complex on the wafer surface could not be effectively removed, leading to the contamination of the silver layer by residual impurities across processes. This made it difficult to solve the core problems of increased silver layer contact resistance and decreased frequency stability.

[0064] In Comparative Example 2, because no electronic-grade nano-Al2O3 was added to the composite barrier liquid, it lacked the strengthening effect on the barrier membrane structure, resulting in insufficient membrane density. This made it difficult to effectively block the potassium ion penetration path, increasing the risk of cross-process structural damage to the silver layer and failing to fully guarantee the long-term reliability of the crystal.

[0065] In Comparative Example 3, due to the lack of electronic-grade BHT hydrogen polymerization inhibitor in the composite barrier liquid, the barrier film is prone to reduction and deterioration during high-temperature aging, resulting in weakened protective performance of the film layer, difficulty in inhibiting silver layer oxidation reaction, and inability to alleviate the frequency stability risks caused by oxidation.

[0066] In Comparative Example 4, because pure nitrogen was used instead of the nitrogen-hydrogen-argon mixed atmosphere, the antioxidant protection of hydrogen was lacking. The risk of oxidation of the silver layer increased during high-temperature aging, making it difficult to improve the problems of silver layer structural damage and decreased conductivity, thus affecting the stability of the crystal in use.

Claims

1. A kHz crystal frequency electronic component production process, comprising wafer cleaning, plating, coarse adjustment, wafer mounting, curing, frequency adjustment, pressing, pin cutting, reflow, wafer sleeving, and aging procedures, characterized in that: S1. The wafer cleaning procedure comprises five steps of pre-chelation, main cleaning, solvent replacement, weak acid washing, and ultrapure water washing; in the main cleaning step, a composite cleaning solution is used, which comprises potassium hydroxide, EDTA tetrasodium, sodium silicate, and methyl isobutyl ketone; after the ultrapure water washing, the potassium ion concentration is ≤0.1 ppm, the TOC concentration is ≤5 ppb, the methyl isobutyl ketone residue is ≤0.1 ppb, and the isopropyl alcohol residue is ≤0.3 ppb; S2. In the process from solvent replacement to plating, first, argon-oxygen mixed plasma pre-cleaning is performed, and then pure argon activation is performed; after the activation, the wafer is immersed in a composite barrier solution for treatment, and then dried to form a composite barrier film; the composite barrier solution comprises KR-38S, electronic-grade nano-Al2O3, and electronic-grade BHT hydrogen inhibitor; S3. The aging procedure uses a mixed atmosphere composed of nitrogen, hydrogen, and argon, and a honeycomb-shaped porous flow guide plate is arranged in the aging box. In step S1, the pre-chelation uses a 0.06-0.10wt% EDTA solution; the weak acid washing uses 0.05-0.07wt% dilute sulfuric acid, and the spraying time is 2-4 min. In step S1, the composite cleaning solution contains 0.4-0.5wt% potassium hydroxide, 0.10-0.15wt% EDTA tetrasodium, 0.02-0.04wt% sodium silicate, and 1.5-2.0wt% methyl isobutyl ketone. In step S2, in the argon-oxygen mixed plasma pre-cleaning step, the power is 90-110W, the pressure is 4-6Pa, and the treatment time is 15-25s; in the pure argon activation step, the power is 90-110W, the pressure is 4-6Pa, and the treatment time is 8-12s; in the composite barrier solution, the KR-38S content is 0.20-0.30wt%, the electronic-grade nano-Al2O3 content is 0.06-0.10wt%, the electronic-grade BHT hydrogen inhibitor content is 0.02-0.04wt%, and the solvent is isopropyl alcohol-ultrapure water; the composite barrier solution treatment temperature is 40-50℃, the treatment time is 5-8min; the composite barrier film thickness is 1.8-2.5nm. In step S3, the mixed atmosphere is composed of 97.0-98.0vol% nitrogen, 1.3-2.2vol% hydrogen, and 0.4-1.0vol% argon; the surface of the honeycomb-shaped porous flow guide plate is treated with an electronic-grade SiO2 ALD coating, and the specific steps are as follows: using electronic-grade trichlorosilane and oxygen as precursors, depositing a coating with a thickness of 4-10nm on the surface of the honeycomb-shaped porous flow guide plate at 180-220℃. In step S3, the honeycomb-shaped porous flow guide plate is made of quartz, and it is fixed to the wall of the aging box cavity with quartz bolts, and the gap between the bolts and the wall is filled with high-temperature resistant sealant.

2. The kHz crystal frequency electronic component production process of claim 1, wherein, ​ 3. The kHz crystal frequency electronic component production process of claim 1, wherein, ​ 4. The kHz crystal frequency electronic component production process of claim 1, wherein, ​ ​ ​ ​ ​ 5. The kHz crystal frequency electronic component production process of claim 1, wherein, ​ 6. The kHz crystal frequency electronic component production process of claim 1, wherein, ​ 7. The kHz crystal frequency electronic device production process of claim 1, wherein, ​ 8. The kHz crystal frequency electronic device production process of claim 1, wherein, In step S3, the gas replacement stage controls the gas flow rate to be 6-10 L / min and the time to be 30-40 min, so that the oxygen content in the cavity is ≤35 ppm and the water vapor content is ≤25% RH. The gas flow rate is 2.5-3.5 L / min, and the gas is kept flowing before the temperature is lowered to below 45-55℃.